"Enwau Prydeinig gwyn?" Problematizing the idea of "White British" names and naming practices from a Welsh perspective. (September 2018) - Wheeler, Sara Louise
Our personal names are a potential source of information to those around us regarding several interconnected aspects of our lives, including our: ethnic, geographic, linguistic and cultural community of origin, and perhaps our national identity. However, interpretations regarding identifiably "White British" names and naming practices are problematic, due to the incorrect underlying assumption of a homogeneity in the indigenous communities of 'Britain.' The field of names and naming is a particularly good example of the wide linguistic and cultural chasm between the Welsh and English indigenous 'British' communities, and thus the generally paradoxical concept of "Britishness" in its wider sense. In this paper, I will explore names and naming practices which are particularly distinctive to a Welsh context, thus unearthing and opening up for wider debate the hidden diversity within the assumed and imposed category of "White British privilege."